Anti-slip glaze, glazed ceramic product and preparation method thereof
By using anti-slip glaze and modifiers with specific ratios in ceramic products, the problems of reduced anti-slip performance and poor anti-bacterial performance of ceramic products after encountering water are solved, and the coordinated improvement of anti-slip, anti-bacterial and wear resistance of ceramic products is achieved. As well as the effect of significantly improving water resistance and scrubbing resistance.
Patent Information
- Application Number
- CN202411566620.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The anti-slip performance of existing ceramic products is reduced after encountering water, has poor anti-bacterial properties, and is difficult to coordinate anti-slip, anti-bacterial and wear resistance. The products have poor water resistance and scrubbing resistance.
Using a non-slip glaze, including potassium feldspar, sodium feldspar, lanthanum-doped air knife earth modifier, nano zinc oxide, calcite and zirconium silicate modifier, through specific preparation methods such as ball milling, preheating treatment and Ultrasonic treatment, coordinate and optimize the coordination of raw materials, and improve the performance of ceramic products.
It has achieved excellent antibacterial performance of ceramic products, improved coordination and balance of anti-slip, antibacterial and wear resistance, and significantly improved water resistance and scrubbing stability of the products.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic products, and in particular to an anti-slip glaze, a glazed ceramic product and a preparation method thereof. Background Art
[0002] As people's living standards continue to improve, consumers have more and more functional demands on tile products. In home life, it is inevitable that domestic water and oil stains will be spilled in the kitchen and bathroom, and water will accumulate in the living room and bedroom due to daily cleaning. At present, the anti-slip performance of ordinary ceramic tiles used in households is significantly reduced after contact with water, resulting in poor safety.
[0003] The glaze used in existing ceramic products has poor anti-slip performance, and the antibacterial performance of the products is poor. It is difficult to coordinate and balance the improvement of the anti-slip, antibacterial and wear resistance of the products. In addition, the water resistance and scrub resistance of the products are poor, which limits the use efficiency of the products. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an anti-slip glaze, a glazed ceramic product and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides an anti-slip glaze, comprising the following raw materials in parts by weight:
[0007] 25-35 parts of potassium feldspar, 25-30 parts of sodium feldspar, 10-15 parts of lanthanum-doped air knife soil modifier, 5-8 parts of nano zinc oxide, 4-7 parts of calcite, and 4-6 parts of zirconium silicate performance regulator.
[0008] Preferably, the anti-slip glaze comprises the following raw materials in parts by weight:
[0009] 30 parts of potassium feldspar, 27.5 parts of sodium feldspar, 12.5 parts of lanthanum-doped air knife soil modifier, 6.5 parts of nano zinc oxide, 5.5 parts of calcite, and 5 parts of zirconium silicate performance regulator.
[0010] Preferably, the preparation method of the lanthanum-doped air knife soil modifier is:
[0011] S1: prepare 2-5% by mass sodium dodecylbenzene sulfonate solution and 2-4% by mass chitosan solution;
[0012] 1-3 parts of silane coupling agent KH560, 2-4 parts of sodium dodecylbenzene sulfonate solution and 3-5 parts of aluminum borate whisker agent are sequentially added to 4-7 parts of chitosan solution by weight, and the mixture is fully mixed to obtain a modified solution;
[0013] S2: preheating lanthanum oxide at 55-60°C for 10-15 minutes, and then immersing it in a modification liquid of 4-7 times the total weight of lanthanum oxide and stirring it, and obtaining a lanthanum modification liquid after the stirring is completed;
[0014] S3: 5-8 parts of air knife soil and 5-9 parts of lanthanum modified liquid are mixed and ball milled according to weight, with a ball milling speed of 1500r / min and ball milling for 1h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a lanthanum-doped air knife soil modifier.
[0015] Preferably, the stirring speed of the stirring treatment in S2 is 450-550 r / min, and the stirring time is 20-30 min.
[0016] Preferably, the preparation method of the aluminum borate whisker agent is:
[0017] The aluminum borate whisker is first heat-treated at 210-220°C for 10-15 minutes, and then cooled to 55°C at a rate of 2-5°C / min to obtain heat-treated aluminum borate whisker;
[0018] According to weight, 2-4 parts of nano-alumina and 1-2 parts of stearic acid are added to 4-6 parts of dopamine hydrochloride solution, and then 2-3 parts of sodium silicate solution are added and mixed thoroughly to obtain an ultrasonic liquid;
[0019] The heat-treated aluminum borate whiskers and ultrasonic liquid are ultrasonically treated in a weight ratio of 2:5. After the ultrasonic treatment is completed, the aluminum borate whiskers are washed with water, filtered and dried to obtain an aluminum borate whisker agent.
[0020] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%; the ultrasonic power of the ultrasonic treatment is 500-600W, and the ultrasonic treatment lasts for 20-30min.
[0021] Preferably, the preparation method of the zirconium silicate performance regulator is:
[0022] S11: irradiating zirconium silicate in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated zirconium silicate after the irradiation is completed; mixing the irradiated zirconium silicate with a sufficient amount of sodium citrate solution to obtain a zirconium silicate liquid;
[0023] S12: 5-8 parts of zirconium silicate liquid, 1-3 parts of nano-silica sol, 2-4 parts of carboxymethyl cellulose and 3-5 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a zirconium silicate performance regulator.
[0024] Preferably, the mass fraction of the sodium citrate solution is 4-6%.
[0025] The present invention also provides a method for preparing a non-slip glazed ceramic product, comprising the following steps:
[0026] Step 1: weigh the raw materials in the anti-slip glaze according to weight, and then wet-mill them at a ball milling speed of 1000-1500 r / min for 1 hour to obtain the anti-slip glaze;
[0027] Step 2: Wet-mill 10-15 parts of bentonite, 5-8 parts of talc, 5-8 parts of porcelain stone and 4-7 parts of boron nitride by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a ball mill material;
[0028] Step 3: Press the ball abrasive into shape at a pressure of 10 MPa for 1 hour to obtain a green body; apply anti-skid glaze to the green body at a glaze amount of 500 g / m 2 , and then sintering treatment, the sintering temperature is 1250℃, the sintering is 3h, and the sintering is completed to obtain a ceramic product with anti-slip glaze.
[0029] The present invention also provides a ceramic product, which is prepared by the preparation method of the ceramic product made of anti-slip glaze.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The ceramic product of the present invention is obtained by wet ball milling of bentonite, talcum powder, porcelain stone and boron nitride and then pressing and molding to obtain a green body. The raw materials in the green body are coordinated and matched with each other, and then anti-slip glaze is applied and sintered to obtain a ceramic product with excellent antibacterial performance, improved coordination and balance of anti-slip, antibacterial and wear resistance of the product, and remarkable water resistance and scrub resistance stability of the product;
[0032] 2. The lanthanum-doped air knife soil modifier uses air knife soil as a matrix and adopts lanthanum modified liquid for blending and ball milling treatment. The lanthanum oxide in the lanthanum modified liquid is first preheated at 55-60°C for 10-15min. Through the preheating treatment, the lanthanum oxide and the modified liquid are better coordinated. The silane coupling agent KH560, sodium dodecylbenzene sulfonate solution and aluminum borate whisker agent and chitosan solution in the modified liquid are fully blended. Through the mutual coordination between the raw materials, the aluminum borate whisker agent uses aluminum borate whiskers for heat treatment at 210-220°C for 10-15min, and then cooled to 55°C at a rate of 2-5°C / min to optimize the activity efficiency of the aluminum borate whiskers, and then ultrasonic liquid ultrasonic improvement is used to coordinate and optimize the product performance effect;
[0033] 3. The nano-alumina, stearic acid, dopamine hydrochloride solution and sodium silicate solution in the ultrasonic liquid are fully blended. Through the blending and adjustment of the raw materials, nano-alumina is used as a co-ligand to coordinate and improve the aluminum borate whiskers. Through the whisker-like structure distribution system, the lanthanum-doped air knife soil modifier matrix can be better coordinated with the system raw materials, thereby further improving the performance of the product;
[0034] 4. The zirconium silicate performance modifier is made by irradiating zirconium silicate in a proton irradiation box and then mixing it with sodium citrate solution. The zirconium silicate is optimized and improved to improve its dispersion. At the same time, nano-silica sol, carboxymethyl cellulose and magnesium oxide are blended and ball-milled. The resulting zirconium silicate performance modifier has a better coordination effect with the lanthanum-doped air knife soil modifier, thereby further improving the performance of the product. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The anti-slip glaze of this embodiment includes the following raw materials in parts by weight:
[0037] 25-35 parts of potassium feldspar, 25-30 parts of sodium feldspar, 10-15 parts of lanthanum-doped air knife soil modifier, 5-8 parts of nano zinc oxide, 4-7 parts of calcite, and 4-6 parts of zirconium silicate performance regulator.
[0038] The anti-slip glaze of this embodiment includes the following raw materials in parts by weight:
[0039] 30 parts of potassium feldspar, 27.5 parts of sodium feldspar, 12.5 parts of lanthanum-doped air knife soil modifier, 6.5 parts of nano zinc oxide, 5.5 parts of calcite, and 5 parts of zirconium silicate performance regulator.
[0040] The preparation method of the lanthanum-doped air knife soil modifier of this embodiment is:
[0041] S1: prepare 2-5% by mass sodium dodecylbenzene sulfonate solution and 2-4% by mass chitosan solution;
[0042] 1-3 parts of silane coupling agent KH560, 2-4 parts of sodium dodecylbenzene sulfonate solution and 3-5 parts of aluminum borate whisker agent are sequentially added to 4-7 parts of chitosan solution by weight, and the mixture is fully mixed to obtain a modified solution;
[0043] S2: preheating lanthanum oxide at 55-60°C for 10-15 minutes, and then immersing it in a modification liquid of 4-7 times the total weight of lanthanum oxide and stirring it, and obtaining a lanthanum modification liquid after the stirring is completed;
[0044] S3: 5-8 parts of air knife soil and 5-9 parts of lanthanum modified liquid are mixed and ball milled according to weight, with a ball milling speed of 1500r / min and ball milling for 1h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a lanthanum-doped air knife soil modifier.
[0045] The stirring speed of the stirring treatment in S2 of this embodiment is 450-550 r / min, and the stirring time is 20-30 min.
[0046] The preparation method of the aluminum borate whisker agent of the present embodiment is:
[0047] The aluminum borate whisker is first heat-treated at 210-220°C for 10-15 minutes, and then cooled to 55°C at a rate of 2-5°C / min to obtain heat-treated aluminum borate whisker;
[0048] According to weight, 2-4 parts of nano-alumina and 1-2 parts of stearic acid are added to 4-6 parts of dopamine hydrochloride solution, and then 2-3 parts of sodium silicate solution are added and mixed thoroughly to obtain an ultrasonic liquid;
[0049] The heat-treated aluminum borate whiskers and ultrasonic liquid are ultrasonically treated in a weight ratio of 2:5. After the ultrasonic treatment is completed, the aluminum borate whiskers are washed with water, filtered and dried to obtain an aluminum borate whisker agent.
[0050] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%; the mass fraction of the sodium silicate solution is 3-6%; the ultrasonic power of the ultrasonic treatment is 500-600W, and the ultrasonic treatment is performed for 20-30 minutes.
[0051] The preparation method of the zirconium silicate synergist of this embodiment is as follows:
[0052] S11: irradiating zirconium silicate in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated zirconium silicate after the irradiation is completed; mixing the irradiated zirconium silicate with a sufficient amount of sodium citrate solution to obtain a zirconium silicate liquid;
[0053] S12: 5-8 parts of zirconium silicate liquid, 1-3 parts of nano-silica sol, 2-4 parts of carboxymethyl cellulose and 3-5 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a zirconium silicate performance regulator.
[0054] The mass fraction of the sodium citrate solution of the present embodiment is 4-6%.
[0055] The present invention also provides a method for preparing a non-slip glazed ceramic product, comprising the following steps:
[0056] Step 1: weigh the raw materials in the anti-slip glaze according to weight, and then wet-mill them at a ball milling speed of 1000-1500 r / min for 1 hour to obtain the anti-slip glaze;
[0057] Step 2: Wet-mill 10-15 parts of bentonite, 5-8 parts of talc, 5-8 parts of porcelain stone and 4-7 parts of boron nitride by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a ball mill material;
[0058] Step 3: Press the ball abrasive into shape at a pressure of 10 MPa for 1 hour to obtain a green body; apply anti-skid glaze to the green body at a glaze amount of 500 g / m 2 , and then sintering treatment, the sintering temperature is 1250℃, the sintering is 3h, and the sintering is completed to obtain a ceramic product with anti-slip glaze.
[0059] A ceramic product of this embodiment is prepared by the above-mentioned method for preparing a ceramic product made of anti-slip glaze.
[0060] Example 1: An anti-slip glaze comprising the following raw materials in parts by weight:
[0061] 25 parts of potassium feldspar, 25 parts of sodium feldspar, 10 parts of lanthanum-doped air knife soil modifier, 5 parts of nano zinc oxide, 4 parts of calcite, and 4 parts of zirconium silicate performance regulator.
[0062] The preparation method of the lanthanum-doped air knife soil modifier of this embodiment is:
[0063] S1: prepare 2% sodium dodecylbenzene sulfonate solution and 2% chitosan solution;
[0064] Add 1 part of silane coupling agent KH560, 2 parts of sodium dodecylbenzene sulfonate solution and 3 parts of aluminum borate whisker agent to 4 parts of chitosan solution in sequence by weight, mix well, and obtain a modified solution;
[0065] S2: preheating lanthanum oxide at 55° C. for 10 min, then immersing in a modification solution of 4 times the total weight of lanthanum oxide and stirring, and obtaining a lanthanum modification solution after stirring is completed;
[0066] S3: 5 parts of air knife soil and 5 parts of lanthanum modified liquid are mixed and ball milled according to weight, with a ball milling speed of 1500r / min and ball milling for 1h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a lanthanum-doped air knife soil modifier.
[0067] The stirring speed of the stirring treatment in S2 of this embodiment is 450 r / min, and the stirring is carried out for 20 minutes.
[0068] The preparation method of the aluminum borate whisker agent of the present embodiment is:
[0069] The aluminum borate whisker was first heat-treated at 210°C for 10 minutes, and then cooled to 55°C at a rate of 2°C / min to obtain heat-treated aluminum borate whisker;
[0070] According to weight, 2 parts of nano-alumina and 1 part of stearic acid are added to 4 parts of dopamine hydrochloride solution, and then 2 parts of sodium silicate solution are added and mixed thoroughly to obtain an ultrasonic liquid;
[0071] The heat-treated aluminum borate whiskers and ultrasonic liquid are ultrasonically treated in a weight ratio of 2:5. After the ultrasonic treatment is completed, the aluminum borate whiskers are washed with water, filtered and dried to obtain an aluminum borate whisker agent.
[0072] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%; the mass fraction of the sodium silicate solution is 3%; the ultrasonic power of the ultrasonic treatment is 500W, and the ultrasonic treatment is performed for 20 minutes.
[0073] The preparation method of the zirconium silicate synergist of this embodiment is as follows:
[0074] S11: irradiating zirconium silicate in a proton irradiation box for 10 minutes at an irradiation power of 350 W, and obtaining irradiated zirconium silicate after the irradiation is completed; mixing the irradiated zirconium silicate with a sufficient amount of sodium citrate solution to obtain a zirconium silicate liquid;
[0075] S12: 5 parts of zirconium silicate liquid, 1 part of nano-silica sol, 2 parts of carboxymethyl cellulose and 3 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a zirconium silicate performance regulator.
[0076] The mass fraction of the sodium citrate solution in this embodiment is 4%.
[0077] The present invention also provides a method for preparing a non-slip glazed ceramic product, comprising the following steps:
[0078] Step 1: weigh the raw materials in the anti-slip glaze according to weight, and then wet-mill them at a ball milling speed of 1000 r / min for 1 hour to obtain the anti-slip glaze;
[0079] Step 2: Wet-mill 10 parts of bentonite, 5 parts of talc, 5 parts of porcelain stone and 4 parts of boron nitride by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a ball mill material;
[0080] Step 3: Press the ball abrasive into shape at a pressure of 10 MPa for 1 hour to obtain a green body; apply anti-skid glaze to the green body at a glaze amount of 500 g / m 2, and then sintering treatment, the sintering temperature is 1250℃, the sintering is 3h, and the sintering is completed to obtain a ceramic product with anti-slip glaze.
[0081] A ceramic product of this embodiment is prepared by the above-mentioned method for preparing a ceramic product made of anti-slip glaze.
[0082] Example 2: An anti-slip glaze comprising the following raw materials in parts by weight:
[0083] 35 parts of potassium feldspar, 30 parts of sodium feldspar, 15 parts of lanthanum-doped air knife soil modifier, 8 parts of nano zinc oxide, 7 parts of calcite, and 6 parts of zirconium silicate performance regulator.
[0084] The preparation method of the lanthanum-doped air knife soil modifier of this embodiment is:
[0085] S1: prepare 5% sodium dodecylbenzene sulfonate solution and 4% chitosan solution;
[0086] Add 3 parts of silane coupling agent KH560, 4 parts of sodium dodecylbenzene sulfonate solution and 5 parts of aluminum borate whisker agent to 7 parts of chitosan solution in sequence by weight, mix well, and obtain a modified solution;
[0087] S2: preheating lanthanum oxide at 60° C. for 15 min, then immersing in a modification solution 7 times the total weight of lanthanum oxide and stirring, and obtaining a lanthanum modification solution after stirring is completed;
[0088] S3: 8 parts of air knife soil and 9 parts of lanthanum modified liquid are mixed and ball milled according to weight, with a ball milling speed of 1500r / min and ball milling for 1h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a lanthanum-doped air knife soil modifier.
[0089] The stirring speed of the stirring treatment in S2 of this embodiment is 550 r / min, and the stirring is carried out for 30 minutes.
[0090] The preparation method of the aluminum borate whisker agent of the present embodiment is:
[0091] The aluminum borate whisker was first heat-treated at 220°C for 15 minutes, and then cooled to 55°C at a rate of 5°C / min to obtain heat-treated aluminum borate whisker;
[0092] According to weight, 4 parts of nano-alumina and 2 parts of stearic acid are added to 6 parts of dopamine hydrochloride solution, and then 3 parts of sodium silicate solution are added and mixed thoroughly to obtain an ultrasonic liquid;
[0093] The heat-treated aluminum borate whiskers and ultrasonic liquid are ultrasonically treated in a weight ratio of 2:5. After the ultrasonic treatment is completed, the aluminum borate whiskers are washed with water, filtered and dried to obtain an aluminum borate whisker agent.
[0094] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 6%; the ultrasonic power of the ultrasonic treatment is 600W, and the ultrasonic treatment lasts for 30 minutes.
[0095] The preparation method of the zirconium silicate synergist of this embodiment is as follows:
[0096] S11: irradiating zirconium silicate in a proton irradiation box for 15 minutes at an irradiation power of 400 W, and obtaining irradiated zirconium silicate after the irradiation is completed; mixing the irradiated zirconium silicate with a sufficient amount of sodium citrate solution to obtain a zirconium silicate liquid;
[0097] S12: 8 parts of zirconium silicate liquid, 3 parts of nano-silica sol, 4 parts of carboxymethyl cellulose and 5 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a zirconium silicate performance regulator.
[0098] The mass fraction of the sodium citrate solution in this embodiment is 6%.
[0099] The present invention also provides a method for preparing a non-slip glazed ceramic product, comprising the following steps:
[0100] Step 1: weigh the raw materials in the anti-slip glaze according to weight, and then wet-mill them at a ball milling speed of 1500 r / min for 1 hour to obtain the anti-slip glaze;
[0101] Step 2: Wet-mill 15 parts of bentonite, 8 parts of talc, 8 parts of porcelain stone and 7 parts of boron nitride by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a ball mill material;
[0102] Step 3: Press the ball abrasive into shape at a pressure of 10 MPa for 1 hour to obtain a green body; apply anti-skid glaze to the green body at a glaze amount of 500 g / m 2 , and then sintering treatment, the sintering temperature is 1250℃, the sintering is 3h, and the sintering is completed to obtain a ceramic product with anti-slip glaze.
[0103] A ceramic product of this embodiment is prepared by the above-mentioned method for preparing a ceramic product made of anti-slip glaze.
[0104] Example 3: An anti-slip glaze comprising the following raw materials in parts by weight:
[0105] 30 parts of potassium feldspar, 27.5 parts of sodium feldspar, 12.5 parts of lanthanum-doped air knife soil modifier, 6.5 parts of nano zinc oxide, 5.5 parts of calcite, and 5 parts of zirconium silicate performance regulator.
[0106] The preparation method of the lanthanum-doped air knife soil modifier of this embodiment is:
[0107] S1: prepare 3.5% sodium dodecylbenzene sulfonate solution and 3% chitosan solution;
[0108] Add 2 parts of silane coupling agent KH560, 3 parts of sodium dodecylbenzene sulfonate solution and 3-5 parts of aluminum borate whisker agent to 5.5 parts of chitosan solution in sequence by weight, mix well, and obtain a modified solution;
[0109] S2: preheating lanthanum oxide at 57.5°C for 12.5 minutes, then immersing it in a modification solution 5.5 times the total weight of lanthanum oxide and stirring it, and obtaining a lanthanum modification solution after the stirring is completed;
[0110] S3: 6.5 parts of air knife soil and 7 parts of lanthanum modified liquid are mixed and ball milled according to weight, with a ball milling speed of 1500r / min and ball milling for 1h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a lanthanum-doped air knife soil modifier.
[0111] The stirring speed of the stirring process in S2 of this embodiment is 500 r / min, and the stirring time is 25 min.
[0112] The preparation method of the aluminum borate whisker agent of the present embodiment is:
[0113] The aluminum borate whisker was first heat-treated at 215°C for 12.5 min, and then cooled to 55°C at a rate of 3.5°C / min to obtain heat-treated aluminum borate whisker;
[0114] According to weight, 3 parts of nano-alumina and 1.5 parts of stearic acid were added to 5 parts of dopamine hydrochloride solution, and then 2.5 parts of sodium silicate solution were added and mixed thoroughly to obtain an ultrasonic liquid;
[0115] The heat-treated aluminum borate whiskers and ultrasonic liquid are ultrasonically treated in a weight ratio of 2:5. After the ultrasonic treatment is completed, the aluminum borate whiskers are washed with water, filtered and dried to obtain an aluminum borate whisker agent.
[0116] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%; the mass fraction of the sodium silicate solution is 4.5%; the ultrasonic power of the ultrasonic treatment is 560W, and the ultrasonic treatment lasts for 25 minutes.
[0117] The preparation method of the zirconium silicate synergist of this embodiment is as follows:
[0118] S11: irradiating zirconium silicate in a proton irradiation box for 12.5 minutes at an irradiation power of 375 W, and obtaining irradiated zirconium silicate after the irradiation is completed; mixing the irradiated zirconium silicate with a sufficient amount of sodium citrate solution to obtain a zirconium silicate liquid;
[0119] S12: 6.5 parts of zirconium silicate liquid, 2 parts of nano-silica sol, 3 parts of carboxymethyl cellulose and 4 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a zirconium silicate performance regulator.
[0120] The mass fraction of the sodium citrate solution in this embodiment is 5%.
[0121] The present invention also provides a method for preparing a non-slip glazed ceramic product, comprising the following steps:
[0122] Step 1: weigh the raw materials in the anti-slip glaze according to weight, and then wet-mill them at a ball milling speed of 1250 r / min for 1 h to obtain the anti-slip glaze;
[0123] Step 2: Wet-mill 12.5 parts of bentonite, 6.5 parts of talc, 6 parts of porcelain stone and 5.5 parts of boron nitride by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a ball milled material;
[0124] Step 3: Press the ball abrasive into shape at a pressure of 10 MPa for 1 hour to obtain a green body; apply anti-skid glaze to the green body at a glaze amount of 500 g / m 2 , and then sintering treatment, the sintering temperature is 1250℃, the sintering is 3h, and the sintering is completed to obtain a ceramic product with anti-slip glaze.
[0125] A ceramic product of this embodiment is prepared by the above-mentioned method for preparing a ceramic product made of anti-slip glaze.
[0126] Comparative Example 1:
[0127] The difference from Example 3 is that no lanthanum-doped air knife soil modifier is added.
[0128] Comparative Example 2:
[0129] The difference from Example 3 is that no lanthanum modification liquid treatment was used in the preparation of the lanthanum-doped air knife soil modifier.
[0130] Comparative Example 3:
[0131] The difference from Example 3 is that no modification liquid treatment is used in the lanthanum modification liquid.
[0132] Comparative Example 4:
[0133] The difference from Example 3 is that no silane coupling agent KH560 and sodium dodecylbenzene sulfonate solution are added to the modified liquid.
[0134] Comparative Example 5:
[0135] The difference from Example 3 is that no aluminum borate whisker agent is added to the modified solution.
[0136] Comparative Example 6:
[0137] The difference from Example 3 is that no air knife soil is added in the preparation of the lanthanum-doped air knife soil modifier.
[0138] Comparative Example 7:
[0139] The difference from Example 3 is that no zirconium silicate synergist is added.
[0140] Comparative Example 8:
[0141] The difference from Example 3 is that the zirconium silicate synergist is not treated with step S12.
[0142] Comparative Example 9:
[0143] The difference from Example 3 is that magnesium oxide and nano-silica sol are not added in the treatment of step S12.
[0144] Comparative Example 10:
[0145] The difference from Example 3 is that in the preparation of the zirconium silicate performance regulator, the zirconium silicate liquid is made of zirconium silicate and water in a weight ratio of 2:5.
[0146] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were tested for anti-skid, antibacterial and wear resistance under normal conditions. The products were immersed in 55°C water for 12 hours and then scrubbed 10 times with a load of 2N to test the water resistance and scrub resistance stability of the products. The test results are shown in Table 1.
[0147] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 10:
[0148]
[0149] It can be seen from Comparative Examples 1 to 10 and Examples 1 to 3 that the product of Example 3 has an antibacterial rate, and at the same time has excellent anti-slip and wear resistance. The product can achieve coordinated improvement in antibacterial, anti-slip and wear resistance. In addition, the product has excellent performance stability under water resistance and scrub resistance conditions;
[0150] From Comparative Examples 1 to 10 and Example 3, it can be seen that the product performance has a significant trend of deterioration when neither the lanthanum-doped air knife soil modifier nor the zirconium silicate synergist is added. The lanthanum-doped air knife soil modifier and the zirconium silicate synergist are used in combination to achieve a significant performance effect of the product.
[0151] The performance of the products showed a trend of deterioration when the lanthanum modifying liquid was not used for the preparation of the lanthanum-doped air knife soil modifier, the lanthanum modifying liquid was not used for the modification liquid, the silane coupling agent KH560 and the sodium dodecylbenzene sulfonate solution were not added to the modification liquid, the aluminum borate whisker was not added to the modification liquid, and the air knife soil was not added to the preparation of the lanthanum-doped air knife soil modifier. The lanthanum-doped air knife soil modifier obtained by the lanthanum modifying liquid treatment and the air knife soil prepared by the modification liquid obtained by the method of the present invention had the most significant product performance effect. The performance of the product also showed a relatively obvious trend of deterioration when the aluminum borate whisker was not added to the modification liquid.
[0152] The zirconium silicate performance-enhancing agent is not treated with step S12, magnesium oxide and nano-silica sol are not added in the treatment of step S12, and the zirconium silicate liquid in the preparation of the zirconium silicate performance-enhancing agent is prepared by mixing zirconium silicate and water in a weight ratio of 2:5. The performance of the products tends to deteriorate. The product performance effect is most significant when the step S12 treatment is obtained by the specific method of the present invention.
[0153] The present invention finds that the aluminum borate whisker agent has a significant improvement effect on the performance of the product. Based on this, the product performance is further explored through the preparation of the aluminum borate whisker agent.
[0154] Experimental Example 1:
[0155] The only difference from Example 3 is that no heat-treated aluminum borate whiskers are added in the preparation of the aluminum borate whisker agent.
[0156] Experimental Example 2:
[0157] The only difference from Example 3 is that ultrasonic liquid treatment is not used in the preparation of the aluminum borate whisker agent.
[0158] Experimental Example 3:
[0159] The only difference from Example 3 is that no nano-alumina is added to the ultrasonic liquid.
[0160] Experimental Example 4:
[0161] The only difference from Example 3 is that stearic acid and sodium silicate solution are not added to the ultrasonic liquid.
[0162] Experimental Example 5:
[0163] The only difference from Example 3 is that no dopamine hydrochloride solution is added to the ultrasonic liquid.
[0164] The products of Experimental Examples 1 to 5 were tested for anti-skid, antibacterial and wear resistance under normal conditions. The products were immersed in 55°C water for 12 hours and then scrubbed 10 times with a load of 2N to test the water resistance and scrub resistance stability of the products. The test results are shown in Table 2.
[0165] Table 2 Product performance test results of Experimental Examples 1 to 5:
[0166]
[0167] It can be seen from Experimental Examples 1-5 that the performance of the product has a significant tendency to deteriorate when no heat-treated aluminum borate whisker is added in the preparation of the aluminum borate whisker agent. At the same time, the performance of the product also shows an obvious trend of change when ultrasonic liquid treatment is not used in the preparation of the aluminum borate whisker agent. In addition, when nano-alumina is not added to the ultrasonic liquid, stearic acid and sodium silicate solution are not added to the ultrasonic liquid, and dopamine hydrochloride solution is not added to the ultrasonic liquid, the performance of the product all has a tendency to deteriorate to varying degrees. The performance effect of the product using the ultrasonic liquid obtained by the specific method of the present invention in combination with the heat-treated aluminum borate whisker is the most significant, and the effects of other methods are not as obvious as those of the present invention.
[0168] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0169] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An anti-slip glaze, characterized in that: It includes the following raw materials in parts by weight: 25-35 parts of potassium feldspar, 25-30 parts of sodium feldspar, 10-15 parts of lanthanum-doped air knife soil modifier, 5-8 parts of nano zinc oxide, 4-7 parts of calcite, and 4-6 parts of zirconium silicate conditioning agent; The preparation method of the lanthanum-doped air knife soil modifier is: S1: prepare 2-5% by mass sodium dodecylbenzene sulfonate solution and 2-4% by mass chitosan solution; 1-3 parts of silane coupling agent KH560, 2-4 parts of sodium dodecylbenzene sulfonate solution and 3-5 parts of aluminum borate whisker agent are sequentially added to 4-7 parts of chitosan solution by weight, and the mixture is fully mixed to obtain a modified solution; S2: preheating lanthanum oxide at 55-60°C for 10-15 minutes, and then immersing it in a modification liquid of 4-7 times the total weight of lanthanum oxide and stirring it, and obtaining a lanthanum modification liquid after the stirring is completed; S3: 5-8 parts of air knife soil and 5-9 parts of lanthanum modified liquid are mixed and ball milled according to weight, with a ball milling speed of 1500r / min for 1h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain an air knife soil modifier doped with lanthanum; The preparation method of the aluminum borate whisker agent is: The aluminum borate whisker is first heat-treated at 210-220°C for 10-15 minutes, and then cooled to 55°C at a rate of 2-5°C / min to obtain heat-treated aluminum borate whisker; According to weight, 2-4 parts of nano-alumina and 1-2 parts of stearic acid are added to 4-6 parts of dopamine hydrochloride solution, and then 2-3 parts of sodium silicate solution are added and mixed thoroughly to obtain an ultrasonic liquid; The heat-treated aluminum borate whiskers and the ultrasonic liquid are ultrasonically treated in a weight ratio of 2:5, and after the ultrasonic treatment is completed, the aluminum borate whiskers are washed with water, filtered and dried to obtain an aluminum borate whisker agent; The preparation method of the zirconium silicate synergist is as follows: S11: irradiating zirconium silicate in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated zirconium silicate after the irradiation is completed; mixing the irradiated zirconium silicate with a sufficient amount of sodium citrate solution to obtain a zirconium silicate liquid; S12: 5-8 parts of zirconium silicate liquid, 1-3 parts of nano-silica sol, 2-4 parts of carboxymethyl cellulose and 3-5 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a zirconium silicate performance regulator.
2. The anti-slip glaze according to claim 1, characterized in that: The anti-slip glaze comprises the following raw materials in parts by weight: 30 parts of potassium feldspar, 27.5 parts of sodium feldspar, 12.5 parts of lanthanum-doped air knife soil modifier, 6.5 parts of nano zinc oxide, 5.5 parts of calcite, and 5 parts of zirconium silicate performance regulator.
3. The anti-slip glaze according to claim 1, characterized in that: The stirring speed of the stirring treatment in S2 is 450-550 r / min, and the stirring is performed for 20-30 min.
4. The anti-slip glaze according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%; the ultrasonic power of the ultrasonic treatment is 500-600W, and the ultrasonic treatment lasts for 20-30 minutes.
5. The anti-slip glaze according to claim 1, characterized in that: The mass fraction of the sodium citrate solution is 4-6%.
6. A method for preparing a ceramic product made of anti-slip glaze, using the anti-slip glaze according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: weigh the raw materials in the anti-slip glaze according to weight, and then wet-mill them at a ball milling speed of 1000-1500 r / min for 1 hour to obtain the anti-slip glaze; Step 2: Wet-mill 10-15 parts of bentonite, 5-8 parts of talc, 5-8 parts of porcelain stone and 4-7 parts of boron nitride by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a ball mill material; Step 3: Press the ball abrasive into shape at a pressure of 10 MPa for 1 hour to obtain a green body; apply anti-skid glaze to the green body at a glaze amount of 500 g / m 2 , and then sintering treatment, the sintering temperature is 1250℃, the sintering is 3h, and the sintering is completed to obtain a ceramic product with anti-slip glaze.
7. A ceramic product prepared by the method for preparing a ceramic product made of anti-slip glaze according to claim 6.
Citation Information
Patent Citations
Anti-slip protective glaze, anti-slip stain-resistant ceramic tile and preparation method of anti-slip stain-resistant ceramic tile
CN116282921A